Photoluminescence Properties of Two Closely Related Isostructural Series Based on Anderson-Evans Cluster Coordinated With Lanthanides [Ln(H2O)7{X(OH)6Mo6O18}]•yH2O, X = Al, Cr - Tewari, Shailabh; Adnan, Mohammad; Balendra,; Kumar, Vineet; Jangra, Gaurav; Prakash, Gaddam Vijaya; Ramanan, Arunachalam (Frontiers in Chemistry, 2019)
The paper describes synthesis of the whole series of two structurally related lanthanide coordinated chromium or aluminum hexamolybdates (Anderson-Evans cluster) including eleven new members hitherto unreported: [Ln(OH2)7{X(OH)6Mo6O28}].4H2O and [(OH2)7Ln{X(OH)6Mo6O28}Ln(OH2)7]{ X(OH)6Mo6O28}.16H2O where X = Al or Cr and Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Y. Crystal structures of all the solids were established by powder and single crystal X-ray diffraction techniques. The two series are dictated by a different supramolecular aggregation of the same set of molecular species: Lighter lanthanides favor coordination interaction between lanthanide ions and molybdate cluster forming 1D chains while the heavier lanthanides result in molecular solids (0D) interacting through nonbonding interactions. The reaction with Er and Tm leads to a concomitant mixture of series I and II. Photoluminescence of the single crystals of all chromium molybdates was dominated by a ruby-like emission including those which contain optically active ions Pr, Sm, Eu, Tb, Dy and Tm. Aluminum analogues containing optically active lanthanide ions showed photoluminescence with its well-known characteristic emissions. Our results strongly suggest a possible energy transfer between lanthanide ions to chromium levels for the quenching of lanthanide emission in lanthanide coordinated chromium molybdates. Intensity measurements showed that the emission from chromium molybdates are almost two orders of magnitude lower than naturally occurring ruby with broader line widths at room temperature.